Penerapan Model Pembelajaran Tipe Student Facilitator and Explaining (SFAE) dalam Meningkatkan Etika Berbicara - Nixon Lumban Gaol (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2020)
This research was conducted by applying the Student Facilitator and Explaining type of Cooperative Learning model in Christian Religious Education learning to improve speaking ethics of class IX-2 students of SMP Negeri 1 Sibolangit in 2020. The type of research used was Classroom Research Action. The low ethics of students in speaking is due to the influence of globalization of western culture, as well as the lack of attention from parents and the environment about the importance of speaking ethics, thus fading Indonesian culture. Therefore, the low ethics of speaking to students cannot be ignored, because if left unchecked, our good cultural ethics as Indonesians will fade away, due to the influence of globalization and the environment and parents who are less supportive of speaking. good. Based on the results of the analysis in this study, it can be concluded that the application of the cooperative learning model type Student Facilitator And Explaining can improve students' speaking ethics in Christian Religious Education learning in class IX-2 SMP Negeri 1 Sibolangit. Abstrak Penelitian ini dilakukan dengan menerapkan model Pembelajaran Kooperatif tipe Student Facilitator and Explaining dalam pembelajaran Pendidikan Agama Kristen untuk meningkatkan etika berbicara siswa kelas IX-2 SMP Negeri 1 Sibolangit tahun 2020. Jenis penelitian yang digunakan adalah Classroom Research Action. Rendahnya etika siswa dalam berbicara dikarenakan pengaruh globalisasi budaya barat, serta kurangnya perhatian orang tua dan lingkungan tentang pentingnya etika berbicara, sehingga melunturkan budaya Indonesia. Oleh sebab itu, rendahnya etika berbicara pada siswa tidak dapat dibiarkan begitu saja, karena jika dibiarkan begitu saja maka etika budaya yang baik kita anut sebagai orang Indonesia akan luntur begitu saja, karena adanya pengaruh globalisasi dan lingkungan serta orang tua yang kurang mendukung untuk berbicara yang baik. Berdasarkan hasil analisis pada penelitian ini dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe Student Facilitator And Explaining dapat meningkatkan etika berbicara siswa pada pembelajaran Pendidikan Agama Kristen di kelas IX-2 SMP Negeri 1 Sibolangit.